Seed inoculation with Azospirillum brasilense in corn plants submitted to water limitation - Coelho, Antônio Eduardo; Tochetto, Cláudia; Turek, Thais Lemos; Michellon, Luiz Henrique; Fioreze, Samuel Luiz (Scientia Agraria Paranaensis, 2017)
The objective of this work was to evaluate the seed inoculation with Azospirilum brasilense in corn plants under limitation of the water supply. Two assays were carried out in greenhouse conditions, using low nitrogen substrate pots. To the first assay, corn seeds were inoculated or not with A. brasilense and treated or not with a biostimulant (IBA + KT + GA). At the second assay, two corn genotypes were inoculated or not with A. brasilense. In both assays, plants were submitted to limited condition of water supply at initial vegetative growth. During this period, gas exchange parameters were determined at the plants. After stress period, dry matter and nitrogen content were determined in roots and above ground parts of the plants. In addition, substrate nitrogen content was determined. It was observed effects of water restriction supply for gas exchange parameters and dry matter accumulation. Corn seed inoculation with A. brasilense did not affect plant responses to water limitation; neither improves the nitrogen content on substrate or plants.